Effect of industrial grade chitosan on the ripening period of newly harvested mango (Mangifera indica Linn. CV. carabao) - Tayona, John Earl Peregrino
Newly harvested carabao mangoes were treated with industrial grade chitosan, a polysaccharide derived from shellfish wastes, to evaluate its effect on the fruit's ripening period.